2019
DOI: 10.1155/2019/1245072
|View full text |Cite
|
Sign up to set email alerts
|

CDK1, CCNB1, CDC20, BUB1, MAD2L1, MCM3, BUB1B, MCM2, and RFC4 May Be Potential Therapeutic Targets for Hepatocellular Carcinoma Using Integrated Bioinformatic Analysis

Abstract: Hepatocellular carcinoma (HCC) is a malignant tumor with high mortality. The abnormal expression of genes is significantly related to the occurrence of HCC. The aim of this study was to explore the differentially expressed genes (DEGs) of HCC and to provide bioinformatics basis for the occurrence, prevention and treatment of HCC. The DEGs of HCC and normal tissues in GSE102079, GSE121248, GSE84402 and GSE60502 were obtained using R language. The GO function analysis and KEGG pathway enrichment analysis of DEGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 39 publications
10
54
0
Order By: Relevance
“…Inhibition of CDC20 expression in HCC reduced cell proliferation and induced G2/M cell cycle arrest, showing a positive correlation with TNM staging [ 30 ]. Consistent with our research findings, increased expression of BUB1B is associated with poor prognosis in HCC patients [ 31 ]. KIF11 is highly expressed in blast crisis chronic myelogenous leukemia [ 32 ] and pancreatic cancer [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of CDC20 expression in HCC reduced cell proliferation and induced G2/M cell cycle arrest, showing a positive correlation with TNM staging [ 30 ]. Consistent with our research findings, increased expression of BUB1B is associated with poor prognosis in HCC patients [ 31 ]. KIF11 is highly expressed in blast crisis chronic myelogenous leukemia [ 32 ] and pancreatic cancer [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…MCM2 was considered as a potential therapeutic target for cancer treatment, and the level of MCM2 could predict poor prognosis for osteosarcoma [ 21 ], gastric cancer [ 22 ], lung adenocarcinoma [ 23 ], diffuse large B cell lymphoma [ 24 ], and esophageal cancer [ 25 ]. Recent research suggested that MCM2 might be a potential therapeutic target for HCC [ 26 ]. Furthermore, Deng et al found that MCM2 inhibition could increase the sensitivity of carboplatin in ovarian cancer cell [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, EZH2 also displayed higher expression in tumor tissues compared with adjacent tissues; however, the overall survival assay showed no difference between positive and negative-EZH2. A bioinformatic study on HCC disclosed overexpression of The cell-division cycle protein 20 (CDC20), MAD2L1, and DNA replication licensing factor (MCM3) could predict poor prognosis [32,33]. In our study, partially due to limited clinical samples, CDC20 and MCM3 showed no difference in overall survival analysis.…”
Section: Discussionmentioning
confidence: 55%